Positive electrode active material and preparation method thereof, positive electrode plate, battery and application

By modifying ammonium phosphomolybdate on lithium iron phosphate and adopting a double-layer cladding structure of carbon and gallium nitride, the problem of decreasing cycle stability of the positive electrode material in the prior art when improving the rate performance is improved, and high rate performance is achieved and cycle stability.

CN119315008APending Publication Date: 2025-01-14HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411435222.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When the existing lithium iron phosphate lithium battery positive electrode materials improve the rate performance, the cycle stability and service life will be reduced due to the addition of doped elements, and the improvement of the rate performance of doped elements is limited.

Method used

Using the ammonium phosphodymium modified lithium iron phosphate as the core, combined with the double-layer coating structure of carbon and gallium nitride to form the positive electrode active material of lithium iron phosphate modified by ammonium phosphodymium, and ammonium phosphodymium is generated by in-situ synthesis method. It can modify lithium iron phosphate to improve its cycle stability and rate performance.

Benefits of technology

The cycle stability and rate performance of the positive electrode active material are significantly improved, the conductivity and structural stability of the material are ensured, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315008A_ABST
    Figure CN119315008A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive active material and a preparation method thereof, a positive pole piece, a battery and application. The positive electrode active material comprises an inner core and a coating layer coating the inner core; the inner core is lithium iron phosphate modified by ammonium phosphomolybdate; the coating layer comprises a first carbon coating layer, a gallium nitride coating layer and a second carbon coating layer; the first carbon coating layer is arranged on the surface of the inner core, the gallium nitride coating layer is arranged on the surface, deviating from the inner core, of the first carbon coating layer, and the second carbon coating layer is arranged on the surface, deviating from the inner core, of the gallium nitride coating layer. The positive electrode active material provided by the invention has very high cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and specifically to a positive electrode active material and a preparation method, a positive electrode sheet, a battery, and applications. Background Art

[0002] The commonly used lithium battery positive electrode material lithium iron phosphate (LiFePO4) has the characteristics of high thermal stability and long cycle life, but low rate performance. The common way to improve its rate performance is to dope it with metals (such as manganese, cobalt, nickel, aluminum, titanium, etc.) or non-metals (such as nitrogen, sulfur, fluorine, etc.). Although it can effectively improve the conductivity and ion diffusion coefficient of lithium iron phosphate, thereby improving its rate performance, its cycle stability and service life will be reduced due to the doping of elements. In addition, doping elements also have limited effect on improving rate performance.

[0003] Therefore, it is necessary to find materials that can significantly improve the rate performance of lithium iron phosphate without reducing the cycle stability. Summary of the invention

[0004] In order to solve the above problems, the present application proposes a positive electrode active material and a preparation method, a positive electrode sheet, a battery, and an application. The positive electrode active material has high cycle stability and rate performance.

[0005] This application is implemented through the following technical solutions:

[0006] In a first aspect, the present application provides a positive electrode active material, comprising a core and a coating layer coating the core;

[0007] The core is lithium iron phosphate modified by ammonium phosphomolybdate;

[0008] The coating layer comprises a first carbon coating layer, a gallium nitride coating layer, and a second carbon coating layer;

[0009] The first carbon coating layer is disposed on the surface of the core, the gallium nitride coating layer is disposed on the surface of the first carbon coating layer away from the core, and the second carbon coating layer is disposed on the surface of the gallium nitride coating layer away from the core;

[0010] The molar ratio of the lithium iron phosphate to the ammonium phosphomolybdate is 7:0.01-0.02.

[0011] In the positive electrode active material of the present application, the molybdenum element can improve the ionic conductivity of the positive electrode active material and enhance the cycle performance of the positive electrode active material; the ammonium phosphomolybdate has a cage structure with high symmetry and stability. In the lithium iron phosphate modified by ammonium phosphomolybdate, the lithium ions are located in the gap of the crystal structure formed by the cage structure modifying the lithium iron phosphate olivine structure, which is easy to embed and remove, effectively improving the cycle stability and rate performance of the positive electrode active material; the carbon coating layer and the gallium nitride coating layer not only improve the conductivity of the positive electrode active material, but also protect the material coated therein, so that the structure of the material is not easily destroyed. The positive electrode active material described in the present application has high cycle stability and rate performance.

[0012] In some possible implementations, the first carbon coating layer is at least one layer, and the thickness of the single carbon coating layer is 5 nm to 20 nm.

[0013] In some possible implementations, the second carbon coating layer is at least one layer, and the thickness of the single carbon coating layer is 5 nm to 20 nm.

[0014] In some possible implementations, the gallium nitride coating layer is at least one layer, and the thickness of the single gallium nitride coating layer is 2 nm to 10 nm.

[0015] In some possible implementations, the tap density of the positive electrode active material is 0.8 g / cm 3 ~1.35g / cm 3 .

[0016] In a second aspect, the present application proposes a method for preparing a positive electrode active material, comprising the following steps:

[0017] Adding phosphoric acid to the suspension to carry out a synthesis reaction to obtain a precursor; wherein the components in the suspension include lithium iron phosphate and ammonium molybdate;

[0018] The precursor is dried, washed, spray-dried, and then subjected to a first carbon coating, a gallium nitride coating, and a second carbon coating to obtain a positive electrode active material.

[0019] The preparation method of the positive electrode active material of the present application comprises the following steps: in a synthesis reaction, ammonium molybdate and phosphoric acid are used to synthesize ammonium phosphomolybdate in situ to modify lithium iron phosphate to obtain a precursor; the precursor is dried to remove moisture, excess phosphoric acid and ammonium phosphate are removed by washing, and a first carbon coating layer, a gallium nitride coating layer and a second carbon coating layer are coated after spray granulation to obtain the positive electrode active material; the positive electrode active material has excellent conductivity, cycle stability and rate performance.

[0020] In some possible implementations, the synthesis reaction comprises the steps of:

[0021] adding phosphoric acid to the suspension and stirring to obtain a reaction solution;

[0022] The pH value of the reaction solution is adjusted by a pH adjuster to obtain a precursor with a pH value of 3 to 5.

[0023] In some possible implementations, the molar ratio of the lithium iron phosphate, the ammonium molybdate and the phosphoric acid is 7:(0.12-0.2):(0.02-0.03).

[0024] In some possible implementations, the drying temperature is 100° C. to 150° C., and the drying time is 0.5 h to 3 h.

[0025] In some possible implementations, the spray drying includes pressure spray drying, in which the air inlet temperature is 200° C. to 300° C., the air outlet temperature is 95° C. to 100° C., and the air inlet pressure is 0.2 MPa to 0.6 MPa.

[0026] In a third aspect, the present application proposes a positive electrode plate, wherein the positive electrode plate includes the positive electrode active material described in the present application or the positive electrode active material prepared by the preparation method described in the present application.

[0027] In a fourth aspect, the present application provides a battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;

[0028] The positive electrode plate includes the positive electrode plate described in the present application.

[0029] In the fifth aspect, the present application proposes an application of the positive electrode active material described in the present application, the positive electrode active material prepared by the preparation method of the positive electrode active material described in the present application, the positive electrode plate described in the present application, or the battery described in the present application in household appliances, electric vehicles, electric cars, electric trains, ships, satellites or energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0031] Figure 1 A schematic diagram of a process for preparing a positive electrode active material in an embodiment of the present application;

[0032] Figure 2 This is a SEM image of the positive electrode active material in Example 1 of the present application.

[0033] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0035] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0036] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.

[0037] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX can also be called the second XX, and similarly, the second XX can also be called the first XX. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more of the features.

[0038] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0039] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0040] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0041] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0042] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0043] The chemical formula of the term "ammonium phosphomolybdate" is (NH4)3PMo 12 O 40 (Molar mass is about 1876.37 g / mol), which is a typical Keggin structure.

[0044] Traditional lithium iron phosphate materials are widely used due to their high safety, stability, environmental friendliness and low production cost. However, due to its poor rate performance and low energy density, it must be modified and upgraded to further expand the market. Although lithium iron phosphate can be doped with metal elements (such as manganese, cobalt, nickel, aluminum, titanium, etc.) and / or non-metals (such as nitrogen, sulfur, phosphorus, fluorine, etc.), due to the limitations of the lithium iron phosphate structure (olivine structure) itself, the effect of the doped metal elements on the rate performance and energy density of lithium iron phosphate is limited, and the cycle stability and service life of lithium iron phosphate will be reduced due to the doping of elements.

[0045] The Keggin structure is a basic structural unit consisting of a central atom and four auxiliary atoms surrounding a tetrahedral center. This structure consists of 12 connected five-membered rings and has high stability and reactivity. At present, Keggin structure polyacids have excellent proton conductivity and potential electron conductivity, so they have broad application prospects in materials science, energy technology, catalytic chemistry and other fields. For example, they can be used as solid electrolyte materials, proton exchange membranes for fuel cells, electrochemical sensors and catalysts. However, due to the difference in electrochemical properties between the Keggin structure and lithium iron phosphate, it has not been used to improve the technical bias in the field of positive electrode active materials.

[0046] In order to effectively exert the electrical properties of the Keggin structure and improve the rate performance and cycle stability of lithium iron phosphate materials, the embodiments of the present application propose a positive electrode active material and preparation method, a positive electrode plate, a battery, and an application. In the positive electrode active material, ammonium phosphomolybdate with a Keggin structure is used to modify the lithium iron phosphate, which effectively improves the cycle stability and rate performance of the battery; the carbon coating layer improves the conductivity of the positive electrode active material. The preparation method uses an in-situ synthesis method to generate ammonium phosphomolybdate from ammonium molybdate and phosphoric acid in situ to modify the lithium iron phosphate, so that the crystal structure of the ammonium phosphomolybdate-modified lithium iron phosphate is more stable, thereby effectively improving the cycle stability and rate performance of the battery.

[0047] The following is a detailed description of a positive electrode active material and a preparation method, a positive electrode sheet, and a battery in an embodiment of the present application.

[0048]

Positive electrode active material

[0049] In a first aspect, an embodiment of the present application provides a positive electrode active material, including a core and a coating layer coating the core;

[0050] The core is lithium iron phosphate modified with ammonium phosphomolybdate;

[0051] The coating layer includes a first carbon coating layer, a gallium nitride coating layer, and a second carbon coating layer;

[0052] The first carbon coating layer is disposed on the surface of the inner core, the gallium nitride coating layer is disposed on the surface of the first carbon coating layer away from the inner core, and the second carbon coating layer is disposed on the surface of the gallium nitride coating layer away from the inner core.

[0053] In the positive active material of the embodiment of the present application, molybdenum can improve the conductivity of the positive active material and enhance the cycle performance of the positive active material; ammonium phosphomolybdate has a cage structure with high symmetry and stability. In the lithium iron phosphate modified by ammonium phosphomolybdate, lithium ions are located in the gap of the crystal structure formed by the cage structure modifying the lithium iron phosphate olivine structure, which is easy to embed and remove, effectively improving the cycle stability and rate performance of the positive active material; the carbon coating layer and the gallium nitride coating layer not only improve the conductivity of the positive active material, but also protect the material coated therein, so that the structure of the material is not easily destroyed. The positive active material of the present application has high cycle stability and rate performance.

[0054] In some embodiments, the average particle size Dv50 of lithium iron phosphate is 1 μm to 5 μm. In the exemplary embodiment, it can be a typical but non-limiting average particle size such as 1 μm, 2.5 μm, 5 μm, or a range between any two average particle sizes. Lithium iron phosphate can be selected from existing commercially available materials or can be prepared as long as it meets the average particle size required by the embodiments of the present application.

[0055] In some embodiments, the molar ratio of lithium iron phosphate to ammonium phosphomolybdate is 7:(0.01-0.02). In exemplary embodiments, the molar ratio may be 7:0.01, 7:0.017, 7:0.02, or other typical but non-limiting molar ratios or a range between any two molar ratios.

[0056] In some embodiments, the first carbon coating layer is at least one layer, and the thickness of the single carbon coating layer is 5 nm to 20 nm. In exemplary embodiments, the thickness can be 5 nm, 10 nm, 20 nm, or other typical but non-limiting thicknesses, or a range between any two thicknesses.

[0057] In some embodiments, the gallium nitride coating layer is at least one layer, and the thickness of the single-layer gallium nitride coating layer is 2nm to 10nm. In the exemplary embodiment, it can be a typical but non-limiting thickness such as 2nm, 5nm, 10nm, 15nm, 30nm, or a range between any two thicknesses.

[0058] In some embodiments, the second carbon coating layer is at least one layer, and the thickness of the single carbon coating layer is 5 nm to 20 nm. In exemplary embodiments, the thickness can be 5 nm, 10 nm, 20 nm, or other typical but non-limiting thicknesses, or a range between any two thicknesses.

[0059] In some embodiments, the tap density of the positive electrode active material is 0.8 g / cm 3 ~1.35g / cm 3 In the example, it can be 0.82 g / cm 3 、0.84g / cm 3 , 0.9g / cm 3 、0.92g / cm 3 、0.94g / cm 3 , 1.12g / cm 3 , 1.22g / cm 3 , 1.25g / cm 3 , 1.35g / cm 3 Typical but non-limiting tap density or a range between any two tap densities. Within this tap density range, the energy density of the battery is effectively increased.

[0060] [A method for preparing a positive electrode active material]

[0061] The second aspect of the present application provides a method for preparing a positive electrode active material, such as Figure 1 As shown, the following steps are included:

[0062] S10. Add phosphoric acid to the suspension to carry out a synthesis reaction to obtain a precursor; wherein the components in the suspension include lithium iron phosphate and ammonium molybdate.

[0063] S20. After drying the precursor, washing, spray drying, and then performing a first carbon coating, a gallium nitride coating, and a second carbon coating to obtain a positive electrode active material.

[0064] The preparation method of the positive electrode active material of the embodiment of the present application comprises the following steps: in a synthesis reaction, ammonium molybdate and phosphoric acid are used to synthesize ammonium phosphomolybdate in situ to modify lithium iron phosphate to obtain a precursor; the precursor is dried to remove moisture, excess impurities such as phosphoric acid and ammonium phosphate are removed by washing, and a first carbon coating layer, a gallium nitride coating layer and a second carbon coating layer are coated after spray granulation to obtain a positive electrode active material; the positive electrode active material has excellent conductivity, cycle stability and rate performance.

[0065] [Step S10]

[0066] In some embodiments, in the above step S10, the preparation of the suspension includes the steps of: mixing ammonium molybdate and water in a preset ratio to obtain an ammonium molybdate solution, and then dispersing lithium iron phosphate in the ammonium molybdate solution under stirring conditions to obtain a suspension.

[0067] In some embodiments, in the above step S10, the suspension further includes a surfactant. The surfactant can promote the uniform dispersion of lithium iron phosphate in the suspension. The material of the surfactant can be any material that meets the requirements, and is not mandatory, but as an example, the surfactant can be sodium dodecylbenzene sulfonate (SDBS), hexadecyltrimethylammonium bromide (CTAB), etc.

[0068] In some embodiments, the mass of the surfactant is 0.1% to 1% of the mass of the lithium iron phosphate. In exemplary embodiments, it can be 0.1%, 0.5%, 1%, or other typical but non-limiting mass percentages or a range between any two mass percentages.

[0069] In some embodiments, the mass fraction of ammonium molybdate in the ammonium molybdate solution is 10% to 28%. In exemplary embodiments, it can be 10%, 15%, 28% or other typical but non-limiting mass fractions or a range between any two mass fractions.

[0070] In some embodiments, in the above step S10, the mixing reaction comprises the steps of:

[0071] S11. Add phosphoric acid to the suspension and stir to obtain a reaction solution.

[0072] S12. Use a pH adjuster to adjust the pH value of the reaction solution to obtain a precursor with a pH value of 3 to 5.

[0073] In the above-mentioned mixing reaction step, phosphoric acid and ammonium molybdate in the suspension react in situ to form ammonium phosphomolybdate having a Keggin structure, and simultaneously modify lithium iron phosphate; adjusting the pH value of the solution to acidity can make the generated Keggin structure more stable.

[0074] In some embodiments, in the above step S11, the reaction temperature of adding phosphoric acid to the suspension is 60°C to 90°C. In the exemplary embodiment, it can be a typical but non-limiting reaction temperature such as 60°C, 70°C, 80°C, 90°C, or a range between any two reaction temperatures. In this case, the temperature reaction is mild, and phosphoric acid and ammonium molybdate synthesize ammonium phosphomolybdate in situ, while modifying lithium iron phosphate.

[0075] In some embodiments, in the above step S11, the stirring speed is 100 rpm to 200 rpm. In the exemplary embodiment, it can be a typical but non-limiting stirring speed such as 100 rpm, 150 rpm, 200 rpm, or a range between any two stirring speeds. In some specific embodiments, when phosphoric acid is added to the mixed solution, the adding speed is 20 d / min to 40 d / min. In the exemplary embodiment, it can be a typical but non-limiting speed such as 20 d / min, 25 d / min, 30 d / min, 35 d / min, 40 d / min, or a range between any two speeds. In this speed range, combined with the stirring speed, precipitation caused by excessive local concentration can be avoided.

[0076] In some embodiments, in the above step S11, the stirring time is 0.5h to 3h, and in the exemplary embodiment, it can be 0.5h, 1h, 2h, 3h, etc., typical but non-limiting time or a range between any two time periods. In this case, phosphoric acid and ammonium molybdate can fully react to form ammonium phosphomolybdate.

[0077] In some specific embodiments, in the above step S12, the pH adjusting agent includes one or more of concentrated ammonia water and dilute nitric acid. In this case, the selection of ammonia water, ammonium nitrate, etc. will not introduce new impurities.

[0078] In some embodiments, in the above step S10, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid is 7:(0.12-0.2):(0.02-0.03), and in the exemplary embodiment, it can be a typical but non-limiting molar ratio such as 7:0.12:0.02, 7:0.2:0.03, or a range between any two molar ratios. In this case, the ammonium molybdate in the solution reacts completely.

[0079] In some embodiments, the mass concentration of phosphoric acid is 60% to 85%. In exemplary embodiments, it can be 60%, 70%, 80%, 85%, etc., which are typical but non-limiting mass concentrations, or a range between any two mass concentrations. In this mass concentration range, the Keggin structure in the prepared precursor is stably modified with lithium iron phosphate.

[0080] [Step S20]

[0081] In some embodiments, in the above step S20, the drying temperature is 100°C to 150°C, and the drying time is 0.5h to 3h; in an exemplary embodiment, the drying temperature can be 100°C, 120°C, 140°C, 150°C, etc., typical but non-limiting temperatures or a range between any two temperatures, and the drying time can be 0.5h, 2h, 3h, etc., typical but non-limiting times or a range between any two times. At this drying temperature and time, the solvent in the precursor is removed.

[0082] In some embodiments, in the above step S20, the dried product is washed with pure water for at least 2 times, and the volume of a single wash is at least 2 times the volume of the product. In this case, the pure water can remove impurities such as excess phosphoric acid and ammonium phosphate contained in the dried product.

[0083] In some embodiments, in the above step S20, spray drying includes pressure spray drying.

[0084] In some embodiments, the air inlet temperature in the pressure spray drying is 200°C to 300°C, the air outlet temperature is 95°C to 100°C, and the air inlet pressure is 0.2MPa to 0.6MPa. In the exemplary embodiment, the air inlet temperature of the spray drying can be a typical but non-limiting temperature such as 200°C, 250°C, 300°C, or a range between any two temperatures, and the air inlet pressure can be a typical but non-limiting time such as 0.2MPa, 0.4MPa, 0.6MPa, or a range between any two pressures. Under this spray granulation temperature and pressure, not only the Keggin structure in the prepared positive electrode active material will not be destroyed, but also the contact interface between lithium iron phosphate and ammonium phosphomolybdate can be stabilized, thereby improving the conductivity and conductivity rate of the positive electrode active material; in addition, the stable contact interface further stabilizes the Keggin structure, so that it will not be destroyed again under the high temperature environment of the subsequent carbon coating step.

[0085] In some specific embodiments, the high pressure gas in the spray drying is compressed air or an inert gas. In this case, the air or the inert gas does not chemically react with the material, and therefore does not generate new impurities.

[0086] In some specific embodiments, the inert gas is at least one of nitrogen, helium, neon, and argon.

[0087] In some specific embodiments, in the above step S20, the average particle size Dv50 of the product obtained by spray drying is 1 μm to 15 μm, and in the exemplary embodiment, it can be a typical but non-limiting average particle size such as 1 μm, 2 μm, 6 μm, 8 μm, 15 μm, or a range between any two average particle sizes. In this case, the particle size range can make the surface of the particles uniformly coated with a carbon coating layer, thereby improving the conductivity of the material.

[0088] In some embodiments, in the above step S20, the ammonium phosphomolybdate-modified lithium iron phosphate is first carbon-coated by chemical vapor deposition. It should be noted that the coating conditions such as gas and temperature of the chemical vapor deposition method can be adjusted according to actual conditions and are not limited. In the embodiment, the deposition temperature of the chemical vapor deposition method is 600°C to 1000°C, which can be a typical but non-restrictive temperature such as 600°C, 650°C, 800°C, 850°C, 900°C, 1000°C, or a range between any two temperatures. In the embodiment, the carbon source of the chemical vapor deposition method includes but is not limited to one or more of methane, ethane, ethylene, and acetylene.

[0089] In other embodiments, in the above step S20, the ammonium phosphomolybdate modified lithium iron phosphate material is first carbon-coated by sintering. It should be noted that the coating conditions of the sintering method can also be adjusted according to actual conditions and are not limited. As an example, the steps of carbon coating by sintering method include: obtaining a glucose mass of 1.5% to 3% of the modified lithium iron phosphate mass, and mixing it with the modified lithium iron phosphate, using pure water as a dispersant, and controlling the solid content (the total mass proportion of glucose and modified lithium iron phosphate) to 33% to 40%, stirring with a sand mill for 40 minutes, spray drying after taking out, and placing the dried material in a kiln for sintering, using argon and other inert gases as protective gas, and controlling the heating rate to 5°C / min to 10°C / min, the constant temperature section to 750°C to 810°C, and the insulation period to 15h to 19h, and cooling naturally. As an example, the carbon source selected for the sintering method can be organic carbon such as glucose, citric acid, sucrose, and white sugar.

[0090] In some embodiments, in the above step S20, the ammonium phosphomolybdate-modified lithium iron phosphate after the first carbon coating is coated with gallium nitride by chemical vapor deposition. It should be noted that the coating conditions of the chemical vapor deposition method can be adjusted according to actual conditions and are not limited. As an example, the step of coating gallium nitride by chemical vapor deposition includes: mixing gallium oxide and ammonium phosphomolybdate-modified lithium iron phosphate particles evenly, growing gallium nitride at 1000°C to 1200°C and in an ammonia atmosphere for 1h to 2h.

[0091] In some embodiments, in the above step S20, the ammonium phosphomolybdate-modified lithium iron phosphate after gallium nitride coating is subjected to a second carbon coating by chemical vapor deposition. It should be noted that the coating conditions such as gas and temperature of the chemical vapor deposition method can be adjusted according to actual conditions and are not limited. In the embodiment, the deposition temperature of the chemical vapor deposition method is 600°C to 1000°C, which can be a typical but non-restrictive temperature such as 600°C, 650°C, 800°C, 850°C, 900°C, 1000°C, or a range between any two temperatures. In the embodiment, the carbon source of the chemical vapor deposition method includes but is not limited to one or more of methane, ethane, ethylene, and acetylene.

[0092] In other embodiments, in the above step S20, the lithium iron phosphate modified with ammonium phosphomolybdate after the gallium nitride coating is subjected to a second carbon coating by a sintering method. It should be noted that the coating conditions of the sintering method can also be adjusted according to actual conditions and are not limited. As an example, the step of carbon coating by the sintering method includes: obtaining a glucose mass of 1.5% to 3% of the mass of the lithium iron phosphate modified with ammonium phosphomolybdate after the gallium nitride coating, and mixing it with the lithium iron phosphate modified with ammonium phosphomolybdate after the gallium nitride coating, using pure water as a dispersant, and controlling the solid content (the total mass proportion of the lithium iron phosphate modified with ammonium phosphomolybdate after the glucose and gallium nitride coating) to 33% to 40%, stirring in a sand mill for 40 minutes, spray drying after taking out, and placing the dried material in a kiln for sintering, using argon or other inert gases as protective gas, and controlling the heating rate to 5°C / min to 10°C / min, the constant temperature section to 750°C to 810°C, the insulation period to 15h to 19h, and cooling naturally. As an example, the carbon source selected for the sintering method can be organic carbon such as glucose, citric acid, sucrose, and white sugar.

[0093]

Positive electrode

[0094] A third aspect of the embodiments of the present application provides a positive electrode plate, which includes the positive electrode active material of the embodiments of the present application or the positive electrode active material prepared by the preparation method of the embodiments of the present application.

[0095] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode film layer disposed on at least one surface of the current collector;

[0096] The positive electrode film layer contains the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.

[0097] In the above-mentioned “at least one surface of the current collector”, the surface refers to the surface of the current collector perpendicular to the thickness direction of the current collector.

[0098] Exemplarily, the thickness of the positive electrode plate is 0.15 mm to 10 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.

[0099] In some embodiments, the current collector material includes one or more of a carbon material, a metal material, and a carbon fiber composite material.

[0100] In some embodiments, the carbon material includes one or more of natural graphite, artificial graphite, carbon black, and carbon fiber.

[0101] In some embodiments, the metal material includes one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, copper, and copper alloy.

[0102] In some embodiments, the positive electrode film layer contains the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.

[0103] In some embodiments, the method for preparing a positive electrode film generally includes:

[0104] The positive electrode slurry containing the positive electrode active material is coated on the current collector, and the positive electrode film layer is obtained through the steps of drying and cold pressing.

[0105] Exemplarily, the thickness of the positive electrode film layer is 0.1 mm to 8 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.

[0106]

Battery

[0107] A fourth aspect of the present application provides a battery, including a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;

[0108] The positive electrode plate includes the positive electrode plate of the embodiment of the present application.

[0109] The battery of the embodiment of the present application has excellent conductivity, cycle stability and rate performance because the positive electrode uses a positive electrode plate containing the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application, thereby making the positive electrode of the battery have excellent conductivity, cycle stability and rate performance.

[0110] In some embodiments, the isolation membrane includes one or more of a porous polymer membrane, a non-woven fabric membrane, and an inorganic composite membrane.

[0111] In some embodiments, the material of the porous polymer membrane includes polyethylene (PE) and / or polypropylene (PP).

[0112] In some embodiments, the material of the non-woven fabric separator includes one or more of polyimide (PI), polyester (such as polyethylene terephthalate PET), cellulose, polyamide (PA), and aramid.

[0113] In some embodiments, the nonwoven membrane is a nanofiber nonwoven membrane, including a polyimide nanofiber membrane. In this case, the nanofiber nonwoven membrane has a higher specific surface area and stronger adsorption capacity, and can more effectively isolate the positive and negative electrodes and promote the transmission of lithium ions.

[0114] In some embodiments, the non-woven membrane is a ceramic-coated non-woven membrane, that is, a ceramic powder (such as Al2O3, SiO2, etc.) is coated on the surface of the non-woven membrane (thickness 2μm to 15μm). This ceramic-coated non-woven membrane not only inherits the high porosity and air permeability of the non-woven fabric, but also increases its thermal stability and mechanical strength.

[0115] In some embodiments, the inorganic composite membrane includes a ceramic-coated composite membrane and an inorganic-organic composite membrane;

[0116] Among them, the ceramic-coated composite membrane is a polymer membrane (such as polyethylene PE, polypropylene PP, etc.) coated with one or more layers of ceramic coating; the ceramic coating can significantly improve the thermal stability and chemical stability of the membrane while maintaining the flexibility and mechanical strength of the polymer membrane;

[0117] Inorganic-organic composite membranes are made by combining inorganic materials with polymer materials through blending, copolymerization or lamination. This composite membrane combines the advantages of inorganic materials and polymer materials and has higher comprehensive performance.

[0118] In some embodiments, the isolation film has a thickness of 60 μm to 100 μm.

[0119] In some embodiments, the negative electrode plate is a common battery plate, generally including a current collector and a negative electrode film layer; the negative electrode film layer contains a negative electrode active material, and the specific negative electrode material and content can be selected according to actual needs without limitation. The preparation of the negative electrode film layer is basically the same as that of the positive electrode film layer.

[0120] In some embodiments, the electrolyte includes an electrolyte salt and a solvent. The materials and contents of the electrolyte salt and the solvent are selected according to actual needs and are not limited.

[0121] The following describes the invention in conjunction with specific embodiments.

[0122] Example 1

[0123] Example 1 provides a method for preparing a positive electrode active material, comprising the following steps:

[0124] (1) A 20% ammonium molybdate solution is prepared with a molar ratio of lithium iron phosphate to ammonium molybdate of 7:0.12 and water as a solvent, and then 0.1% of the mass of lithium iron phosphate is added with hexadecyltrimethylammonium bromide, and the lithium iron phosphate is dispersed in the ammonium molybdate solution under stirring to prepare a suspension.

[0125] (2) At a temperature of 80° C., phosphoric acid with a mass concentration of 85% was added to the suspension, and the mixture was stirred at 180 rpm for 1.5 h to obtain a reaction solution, wherein the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid was 7:0.12:0.03.

[0126] (3) The pH value of the reaction solution was adjusted using concentrated ammonia water to obtain a precursor with a pH value of 4.

[0127] (4) The precursor was dried at 120°C for 2 h; after being washed twice with pure water, it was spray granulated under hot air at 350°C for 5 min.

[0128] (5) Using acetylene as a carbon source, a first carbon coating layer with a thickness of 10 nm is coated on the surface of the spray granulated product by chemical vapor deposition, wherein the deposition temperature is 650° C.

[0129] (6) mixing gallium oxide and lithium iron phosphate particles modified by ammonium phosphomolybdate evenly, growing gallium nitride at 1000° C. in an ammonia atmosphere for 1.5 h to obtain a gallium nitride coating layer with a thickness of 15 nm;

[0130] (7) Glucose is used as a carbon source, and the mass of glucose is 2% of the mass of the ammonium phosphomolybdate-modified lithium iron phosphate coated with gallium nitride; glucose, the ammonium phosphomolybdate-modified lithium iron phosphate coated with gallium nitride and water are mixed and sintered to coat a second carbon coating layer; the environmental conditions during sintering are to use argon or other inert gases as protective gases, the heating rate is controlled at 8°C / min, the constant temperature section is controlled at 790°C, the insulation period is 17h, and it is naturally cooled to obtain a second carbon coating layer with a thickness of 15nm; and the positive electrode active material is obtained.

[0131] Example 1 also provides a positive electrode active material, which is prepared using the preparation method of this example.

[0132] The tap density of the positive electrode active material is 1.74 g / cm 3 .

[0133] Example 2

[0134] Example 2 proposes a positive electrode active material and a preparation method. The material and the preparation steps are basically the same as those in Example 1, except that in the preparation method, the pH value of the precursor is 3.

[0135] The tap density of the positive electrode active material is 1.71 g / cm 3 .

[0136] Example 3

[0137] Example 3 proposes a positive electrode active material and a preparation method. The material and the preparation steps are basically the same as those in Example 1, except that in the preparation method, the pH value of the precursor is 5.

[0138] The tap density of the positive electrode active material is 1.66 g / cm 3 .

[0139] Example 4

[0140] Example 4 proposes a positive electrode active material and a preparation method. The material and the preparation steps are basically the same as those in Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid is 7:0.2:0.03.

[0141] The tap density of the positive electrode active material is 1.63 g / cm 3 .

[0142] Example 5

[0143] Example 5 proposes a positive electrode active material and a preparation method. The material and its preparation steps are basically the same as those in Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid is 7:0.2:0.02; and the pH value of the reaction solution is adjusted to 4 using dilute nitric acid with a concentration of 10%.

[0144] The tap density of the positive electrode active material is 1.67 g / cm 3 .

[0145] Example 6

[0146] Example 6 proposes a positive electrode active material and a preparation method. The material and its preparation steps are basically the same as those in Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid is 7:0.18:0.02; and the pH value of the reaction solution is adjusted to 4 using dilute nitric acid with a concentration of 10%.

[0147] The tap density of the positive electrode active material is 1.69 g / cm 3 .

[0148] Example 7

[0149] Example 7 proposes a positive electrode active material and a preparation method. The material and its preparation steps are basically the same as those in Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid is 7:0.18:0.03; and the pH value of the reaction solution is adjusted to 4 using dilute nitric acid with a concentration of 10%.

[0150] The tap density of the positive electrode active material is 1.72 g / cm 3 .

[0151] Comparative Example 1

[0152] Comparative Example 1 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that the pH value of the precursor is 8.

[0153] Comparative Example 1 also proposes a positive electrode active material, which is prepared by the preparation method of this comparative example. The tap density of the positive electrode active material is 0.99 g / cm 3 .

[0154] Comparative Example 2

[0155] Comparative Example 2 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that the pH value of the precursor is 1.

[0156] Comparative Example 2 also proposes a positive electrode active material, which is prepared by the preparation method of this comparative example. The tap density of the positive electrode active material is 1.01 g / cm 3 .

[0157] Comparative Example 3

[0158] Comparative Example 3 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid is 7:0.12:0.05.

[0159] Comparative Example 3 also proposes a positive electrode active material, which is prepared by the preparation method of this comparative example. The tap density of the positive electrode active material is 1.11 g / cm 3 .

[0160] Comparative Example 4

[0161] The positive electrode active material proposed in Comparative Example 4 is lithium iron phosphate, and the amount used is the same as that in Example 1. The tap density of the positive electrode active material is 1.19 g / cm 3 .

[0162] In order to verify the advancement of the positive electrode active material and the preparation method thereof proposed in the examples of the present application, firstly, taking Example 1 as an example, a scanning electron microscope was used to scan the positive electrode active material prepared in Example 1, and the corresponding Figure 2 The SEM image shown; the positive electrode active materials prepared in the embodiment and the comparative example are then made into button batteries, and the preparation steps are as follows:

[0163] (1) Preparing positive electrode slurry: positive electrode active material: carbon nanotube: polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, and solvent N-methylpyrrolidone (NMP) was added to adjust the viscosity to 4000 mPa·s to 8000 mPa·s to prepare positive electrode slurry.

[0164] (2) The positive electrode slurry is evenly coated on one surface (perpendicular to the thickness direction) of the aluminum foil (positive electrode current collector) and dried, and then rolled and sliced ​​to obtain a positive electrode sheet containing a positive electrode film layer.

[0165] (5) Using lithium hexafluorophosphate-ethyl methyl carbonate as the electrolyte and polypropylene as the isolation membrane, the prepared positive electrode sheet and negative lithium sheet are combined to form a button half-cell.

[0166] The button cell was tested for electrical properties in the voltage range of 2.0V to 3.8V using a Blue Electric device, including 0.1C discharge, 0.1C first charge and discharge efficiency, 5C discharge, and 1C cycle 500 times capacity retention rate. The test results are shown in Table 1 below.

[0167] Table 1

[0168]

[0169] From the above table 1 and Figure 2 At least the following conclusions can be drawn:

[0170] 1) Combine Table 1 and Figure 2 It can be seen that in the positive electrode active material provided in the embodiment of the present application, the double layer of carbon and gallium nitride coated ammonium phosphomolybdate-modified lithium iron phosphate has very high rate performance, electrochemical performance and cycle stability.

[0171] 2) The pH value of the precursor has a great influence on the performance and stability of the positive electrode active material product. Within the pH range of 3 to 5, the ammonium phosphomolybdate-stabilized modified lithium iron phosphate generated, combined with the carbon coating and the gallium nitride coating, makes the prepared positive electrode active material have high cycle stability.

[0172] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: comprising an inner core and a coating layer covering the inner core; The core is lithium iron phosphate modified by ammonium phosphomolybdate; The coating layer includes a first carbon coating layer, a gallium nitride coating layer, and a second carbon coating layer; The first carbon coating layer is disposed on the surface of the core, the gallium nitride coating layer is disposed on the surface of the first carbon coating layer away from the core, and the second carbon coating layer is disposed on the surface of the gallium nitride coating layer away from the core; The molar ratio of the lithium iron phosphate to the ammonium phosphomolybdate is 7:0.01-0.

02.

2. The positive electrode active material according to claim 1, characterized in that The gallium nitride coating layer is at least one layer, and the thickness of the single-layer gallium nitride coating layer is 2nm-10nm.

3. The positive electrode active material according to claim 1, characterized in that The positive electrode active material satisfies at least one of the following (1) to (2): (1) The first carbon coating layer is at least one layer, and the thickness of the single carbon coating layer is 5 nm to 20 nm; (2) The second carbon coating layer is at least one layer, and the thickness of a single carbon coating layer is 5 nm to 20 nm.

4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The tap density of the positive electrode active material is 0.8 g / cm 3 ~1.35g / cm 3 .

5. A method for preparing a positive electrode active material according to any one of claims 1 to 4, characterized in that: The steps include: Adding phosphoric acid to the suspension to carry out a synthesis reaction to obtain a precursor; wherein the components in the suspension include lithium iron phosphate and ammonium molybdate; The precursor is dried, washed, spray-dried, and then subjected to a first carbon coating, a gallium nitride coating, and a second carbon coating to obtain a positive electrode active material.

6. The method for preparing the positive electrode active material according to claim 5, characterized in that: The synthesis reaction comprises the steps of: adding phosphoric acid to the suspension and stirring to obtain a reaction solution; The pH value of the reaction solution is adjusted by a pH adjuster to obtain a precursor with a pH value of 3 to 5.

7. The method for preparing a positive electrode active material according to claim 5, characterized in that: The steps of the preparation method satisfy at least one of the following (1) to (3): (1) The molar ratio of the lithium iron phosphate, the ammonium molybdate and the phosphoric acid is 7:(0.12-0.2):(0.02-0.03); (2) The drying temperature is 100° C. to 150° C. and the drying time is 0.5 h to 3 h; (3) The spray drying includes pressure spray drying, in which the inlet air temperature is 200°C to 300°C, the outlet air temperature is 95°C to 100°C, and the inlet air pressure is 0.2MPa to 0.6MPa.

8. A positive electrode sheet, characterized in that: The positive electrode sheet includes the positive electrode active material according to any one of claims 1 to 4 or the positive electrode active material prepared by the preparation method according to any one of claims 5 to 7.

9. A battery comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte; characterized in that: The positive electrode sheet includes the positive electrode sheet according to claim 8.

10. Use of the positive electrode active material according to any one of claims 1 to 4, the positive electrode active material prepared by the method for preparing the positive electrode active material according to any one of claims 5 to 7, the positive electrode sheet according to claim 8 or the battery according to claim 9 in household appliances, electric vehicles, electric cars, electric trains, ships, satellites or energy storage systems.

Citation Information

Cited By

  • Low-residual-alkali high-nickel positive electrode material and preparation method thereof, positive electrode and battery

    CN119812301A